Effects of exposures to weak 2-Hz vs. 8-Hz electromagnetic fields on spectral characteristics of the electroencephalogram in afternoon nap. Issue 7 (3rd July 2022) - Dorokhov, Vladimir B.; Taranov, Anton O.; Sakharov, Dmitry S.; Gruzdeva, Svetlana S.; Tkachenko, Olga N.; Arsenyev, Gleb N.; Ligun, Natalya V.; Sveshnikov, Dmitry S.; Bakaeva, Zarina B.; Dementienko, Valeriy V.; Puchkova, Alexandra N.
ABSTRACT: The human brain seems to be able to respond to low-level extremely low-frequency electromagnetic fields. Controlled laboratory studies of human sleep under exposure to such fields are scarce, especially on the effects of 1 Hz – 16 Hz fields overlapping with the frequencies of the electroencephalographic (EEG) signal (e.g., delta, theta, alpha, and sigma activities). In a double-blind placebo-controlled study, we examined the effects of exposure to low-level electromagnetic fields of frequencies 2 Hz and 8 Hz on the EEG power density spectra in the range from 1 Hz to 16 Hz and sleep structure. Sleep of 14 young healthy volunteers was polysomnographically recorded during three 50-min afternoon naps (either without exposure or with 2 Hz/0.004 μT or 8 Hz/0.004 μT electromagnetic field). During the first 30 min of a nap the sham, 2 Hz or 8 Hz/0.004 μT exposures had the same effect. For the remaining 20 min, amount of stage 3 sleep and powers in 1 Hz-8 Hz range continued to build up under the 8 Hz/0.004μT and, especially, under the 2 Hz/0.004 μT exposure, whereas they did not change in the sham condition. Therefore, the low-level 2 Hz electromagnetic fields might stimulate deep sleep in the afternoon nap.